Reproductive Technology Application for Increasing Production Performance of Buffalo in Indonesia - I Gede Putu (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2003)
Research activities on buffalo (Bubalus bubalis) has been widely neglected compared to other animal such as cattle, sheep, goat and poultry not only in Indonesia but also in other ASEAN countries. Buffalo is classified as valuable asset for farmers as sources of additional income, meat and draught animal power in agricultural cultivable land. For the last five years, the buffalo population in Indonesia significantly declined form 3,3 million in 1997 to 2,3 millions in 2001, it is urgently required to accelerate research activities using the existing reproductive technologies to increase productive performances in line with increasing demand for meat. Reproductive technologies produced by the Research Institute for Animal Production Bogor and other  Institutions in  Indonesia, including estrus  synchronization for  non  cyclic  buffalo, semen  preservation and  artificial insemination, embryo transfer as well as and feeding management could be directly implemented to field conditions to increase productive performance of buffalo in Indonesia.   Key words: Buffalo, technology, reproductive, productive performance